THE DEVELOPMENT OF MOMENTUM CONSERVATION LAW LABORATORY KIT BY USING TRACKER SOFTWARE AS LEARNING TOOL OF PHYSICS AT SMAN 12 SURABAYA - KURNIAWAN RAMADHANI, WACHID (Inovasi Pendidikan Fisika, 2017)
A learning tool is considered can help students to understand the physics phenomenon. A learning tool in a class has to provide activities to promote students’ knowledge and skills. The final project reported in this publication is intended to develop a certain laboratory kit which was integrated with Tracker Software and acted as the learning tool. This certain kit is projected to help students’ understanding in the concept of Momentum conservation law. The aspect of validity, effectiveness, and practicability of the developed kit were examined by research and development (R&D) method. In this case, the first prototype kit was validated to the two experts before being tested to limited number of students, and the feedback was used to upgrade the preciseness and the accuracy of the kit. Fifteen number of senior high school students in Science-2 class participated in this research for two weeks. The result revealed that the overall students’ achievement is 87 %. This percentage is above the minimum standard score. In addition, both students’ knowledge and skills in operating and analyzing the experimental results have passed the minimum standard score. Having the above results, the developed kit can be regarded as an effective learning tool. The students’ feedback also indicated that the kit is practical with score 92 % (very good). Moreover, according to the two validators this developed kit is valid by percentage of 87.5 % (very good). Therefore, the developed kit is applicable to support students’ understanding in Momentum conservation law concept. Keywords: laboratory kit, Tracker software, Momentum conservation law concept.